Performance Study of IOT Connectivity: Lora Network - Siow, Jia Yie (2020)
The deployment of wireless sensor networks (WSNs) yields a convenient and economical solution for collecting information automatically. However, there are several limitations such as wide geographic area, bandwidth scarcity, lack of network infrastructure and shortage of power supply. Long range (LoRa) is one of the most promising low power wide area network (LPWAN) technologies that allow long-range transmissions. LoRa can be classified into two parts, namely LoRa at physical layer and Long Range Wide Area Network (LoRaWAN) at data link layer. Such architecture motivates the study of two use cases in this thesis. In the first scenario, LoRA gateway and node are implemented in order to evaluate the system performance of LoRaWAN in an indoor environment. The impacts on airtime, received signal strength indicator (RSSI) and signal-to-noise ratio (SNR) are explored under different spreading factors (SF) and transmission distances. In the second scenario, the LoRaWAN environment is shifted to Long Range Peer to Peer (LoRa P2P) image transmission that involves only the LoRa physical layer. Two nodes are set up in this scenario. Constrained by LoRA maximum transmission unit (MTU), images are segmented into multiple packets, which are transferred by either stop-and-wait protocol or LoRa Multi-Packet Transmission Protocol. As in the first scenario, similar performance metrics are assessed. Experimental results from these two studies reveal that LoRA transmissions using LoRAWAN and LoRA P2P are feasible, as long as the distance is within 35m in an indoor environment.